(untitled) - Caliandro, Arthur (New York, 2000)
Dr. Arthur Caliandro is one of America's most trusted and revered spiritual advisers. Now Dr. Caliandro shares his philosophy of hope with the world in this life-enhancing, action-oriented book. It offers 16 simple yet significant steps -- such as beginning a regular spiritual discipline, taking responsibility for your life, and seeking solitude -- that can be put into practice immediately for a abundant life.
Keywords: Tâm lý học ứng dụng,Self-actualization (Psychology),Conduct of life,Spiritual formation